Implemetasi Metode Ummi dalam Meningkatkan Kemampuan Membaca Al'Quran pada Santri Kelas Jilid 1 di Tarbiyatul Qur'an Darul Hijroh Surabaya - Mahmudah, Mila; Muchammad Tachrir Syauqi AG (Sekolah Tinggi Agama Islam Taruna Surabaya, 2024)
The Qur'an is the holy book revealed by Allah SWT to the Prophet Muhammad SAW as a guide for all Muslims. Reading and understanding the Qur'an is a crucial obligation for every Muslim. However, the ability to read the Qur'an among the Indonesian population, especially children, is still far from ideal. This situation has prompted the government and educational institutions to seek effective methods to improve Qur'anic reading skills from an early age. Islamic boarding schools (pondok pesantren), as traditional Islamic educational institutions, play a vital role in Qur'anic education. One method used in these institutions is the Ummi method, designed to fAacilitate Qur'anic learning through a systematic approach.This study aims to describe the foundation, implementation, as well as supporting and inhibiting factors of the Ummi method in enhancing the Qur'anic reading skills of first-level students at Madrasah Tarbiyatul Qur'an Darul Hijroh Surabaya in 2024. Using a qualitative approach with descriptive methods, the study reveals that the Ummi method is effective through a gentle, structured, and systematic approach. Supporting factors include distinctive tones and effective classroom management, while challenges include differences in students' concentration levels and limited study time. Family support and adaptive learning strategies are essential to enhance the effectiveness of this method beyond formal learning hours.